2017
DOI: 10.1002/jcb.25883
|View full text |Cite
|
Sign up to set email alerts
|

MiR-338-5p Promotes Inflammatory Response of Fibroblast-Like Synoviocytes in Rheumatoid Arthritis via TargetingSPRY1

Abstract: Our purpose is to study the roles of microRNA-338-5p (miR-338-5p) on the proliferation, invasion, and inflammatory response of fibroblast-like synoviocytes (SFs) in rheumatoid arthritis patients by regulating SPRY1. The target relationship between miR-338-5p and SPRY1 was validated through luciferase reporter system. The expression of miR-338-5p and SPRY1 in synovial tissues and synovial cells were detected using RT-PCR and western blot. The mimics and inhibitors of miR-338-5p were transfected into SFs. MTT, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…a study using different activators of Wnt/β-catenin signaling revealed that Wnt/β-catenin signaling is closely related to trophoblast cell differentiation (35). in addition, decreased expression of WnT2 in the villi of patients with unexplained recurrent spontaneous abortion may cause trophoblast cell dysfunction via suppressing Wnt/β-catenin signaling (36). on this basis, the present study further examined the effects of FaM99a on Wnt/β-catenin signaling activity.…”
Section: Discussionmentioning
confidence: 85%
“…a study using different activators of Wnt/β-catenin signaling revealed that Wnt/β-catenin signaling is closely related to trophoblast cell differentiation (35). in addition, decreased expression of WnT2 in the villi of patients with unexplained recurrent spontaneous abortion may cause trophoblast cell dysfunction via suppressing Wnt/β-catenin signaling (36). on this basis, the present study further examined the effects of FaM99a on Wnt/β-catenin signaling activity.…”
Section: Discussionmentioning
confidence: 85%
“…62 Studies have also found that miR-338-5p is highly expressed in RA. miR-338-5p can promote the proliferation, invasion, and inflammatory response of RA-FLS by directly downregulating the expression of sprouty RTK signaling antagonist 1 ( SPRY1 ), 63 and also promotes the proliferation and migration of RA-FLS by targeting nuclear factor of activated T cells 5 ( NFAT5 ). 64 Although the current findings on the expression of miR-338-5p in RA are contrary, they also illustrate the potential role of miR-338-5p in RA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Even though miR-338-5p has been shown to be related to several human diseases, as well as rheumatoid arthritis [ 33 ], human gastric cancer [ 34 ], pulmonary fibrosis [ 35 ], lung cancer [ 36 ], and glioblastoma [ 37 ], the relationship between miR-338-5p and HS has not been described yet. However, we speculate that miR-338-5p stimulates the cell proliferation, invasion, and the production of cytokines IL-1a, IL-6, and COX2 in HS.…”
Section: Discussionmentioning
confidence: 99%